Peningkatan Hasil Belajar Peserta Didik Menggunakan Model Discovery Learning Pada Pembelajaran Tematik di Kelas V SDN 20 Muara Jambu, Kabupaten Pesisir Selatan - Dara Sukma Sari (Universitas Negeri Padang, 2021)
The purpose of the study was to improve student learning outcomes in thematic learning using the Discovery Learning model in Class V SDN 20 Muara Jambu Kab. South Coast. This type of research is classroom action research (CAR). The approach used is quantitative and qualitative. The subjects of this study were the fifth grade teachers and fifth grade students, and researchers as practitioners. Data analysis used qualitative and quantitative data analysis, and the research instrument used RPP assessment sheets, teacher and student activities, test and non-test sheets. The conclusions of this study are: 1) The assessment of the percentage of RPP has increased from 79% in the first cycle to 95% in the second cycle. 2) The teacher aspect has increased from 81.25% to 93.75%. 3) The student aspect has increased from 81.25% to 93.75%. 4) Student learning outcomes have increased from the first cycle to get the percentage of completeness 76.19% increased to 95.23% in the second cycle.